Divergent Paths: A Comparative Analysis of Bhutan and Nepal’s Strategies in the South Asian Subsystem - Raj, Ramesh Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Background: Small South Asian states like Nepal and Bhutan are between two dominant powers, India and China. Even though their geopolitical situations are similar, their foreign policy actions are very different. To figure out how small states survive and get around hegemonic and competitive subsystems, it's important to know about these differences. Analyzing how small states endure and negotiate hegemonic and competitive subsystems requires an understanding of these distinctions. Methods: This study adopts a qualitative research design and a systemic level of analysis. It utilizes ex post facto methodology to investigate historical and contemporary events in Nepal and Bhutan. Data is from secondary sources, including academic literature, policy documents, and official statements. The research uses Comparative analysis to identify patterns and divergences in strategic behaviour. Results: Nepal has demonstrated a dual strategy of soft balancing and occasional bandwagoning to maintain its autonomy and address regional pressures. Bhutan, on the other hand, has mostly used a consistent alliance and bandwagoning approach, especially when it comes to security and economic support from India. Both states, on the other hand, use multilateralism and identity-based strategies to show that they are independent in the world. Conclusion: The study finds that geopolitical location does not fully determine foreign policy strategies. Internal political dynamics, leadership choices, and historical contexts have a big impact on the different paths that small states with similar structural problems take. Novelty: This study compares two small states that are similar in many ways; small, landlocked and neighbor of India and China. It shows how internal factors and perceived threats affect foreign policy in ways that go beyond structural determinism.